The victim’s right to waiva the complaint - Adnan, Salma; Naser, Allaa (Journal of Legal Sciences, 2022)
Intervention in the criminal case requires examining the evidence examining  the  identity  of  the accused, and  preparing  him  with  all  the  necessary  elements  to  issuing  the  verdict, and  in  view  of  the  procedures that  this  research  takes,  which  may  extend  for  a long  time, thinking  has  turned  toward  dealing  with  the  criminal  case  without  the  criminal  judiciary, and this call  has  escalated  with  the trend  to  give  the  victim  an  important role in politics criminal  justice until it become a real  party in criminal  justice  and in light  of  that, the recognition  of  the important  role  that  can  be  played  by  the  individuals desire to  achieve  criminal  justice, which led to the  development  of  this  justice and in light of  this  development, the only goal of criminal  justice is no longer punishment , but  it has  become the  achievement  of  protection of  the private  rights of individuals and refome the  relationship  between the victim and the accused  is  an important  goal in  this  development  and in this  context  and away  from  the  courts  of  law, the criminal case is terminated by his own will form the victim  alone  and  that  by  relinquishing  his  complaint.